2023
DOI: 10.1186/s12903-023-03027-6
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in the diagnosis of dental diseases on panoramic radiographs: a preliminary study

Abstract: Background Artificial intelligence (AI) has been introduced to interpret the panoramic radiographs (PRs). The aim of this study was to develop an AI framework to diagnose multiple dental diseases on PRs, and to initially evaluate its performance. Methods The AI framework was developed based on 2 deep convolutional neural networks (CNNs), BDU-Net and nnU-Net. 1996 PRs were used for training. Diagnostic evaluation was performed on a separate evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Our study supports the thesis of high AI performance in CBCT evaluation. The reported sensitivity of PL detection is in line with that of other studies [31,[50][51][52][53]. A study by Orhan et al [31] showed that Diagnocat achieved 92.8% accuracy in PL detection on CBCT images.…”
Section: Discussionsupporting
confidence: 87%
“…Our study supports the thesis of high AI performance in CBCT evaluation. The reported sensitivity of PL detection is in line with that of other studies [31,[50][51][52][53]. A study by Orhan et al [31] showed that Diagnocat achieved 92.8% accuracy in PL detection on CBCT images.…”
Section: Discussionsupporting
confidence: 87%
“…Within this subset, 67 literature reviews, 46 editorials, and 37 seminar articles were excluded, aligning with the study's focus on primary research articles. This comprehensive curation and scrutiny culminated in the inclusion of nine in-vitro papers [ [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ] in the review, which met the specified eligibility criteria. Table 3 presents the overview of the included in-vitro papers [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ].…”
Section: Resultsmentioning
confidence: 99%
“… Verhelst et al [ 34 ] 160 CBCT scans Automatic creation of 3D surface models of the human mandible from CBCT images Layered deep learning algorithm Anonymized full skull CBCT scans Time for segmentation: 17s, IoU: 94.6 %, DSC: 94.4 %, HD: Not specified AI exhibited significantly faster mandible surface model creation with comparable accuracy. Zhu et al [ 35 ] 2278 scans Diagnosis of multiple dental diseases on panoramic radiographs (PRs) BDU-Net, nnU-Net Not specified Sensitivity, Specificity, AUC: Vary by disease, Diagnostic time: Shorter than dentists AI demonstrated comparable or better diagnostic performance in multiple dental disease diagnoses. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mima et al introduced a method utilizing Faster R-CNNs for detecting and classifying tooth regions in dental panoramic X-ray images with high precision and accuracy [ 26 ]. Zhu et al introduced an AI framework for diagnosing common dental diseases from panoramic radiographs, showing high specificity for all diseases except for caries, where it showed lower sensitivity and specificity, but overall, it demonstrated superior diagnostic performance compared to dentists in certain areas [ 27 ].…”
Section: Ai In Oral Radiologymentioning
confidence: 99%